(untitled) (Latakia University Journal -Biological Sciences Series, 2024)
This research was carried out on the coastal water of (AL kornish al janobi)( Southern Corniche) a complement to the previous studies along the Syrian coast. three stations were subject to the effect of sewage. cruises were carried out during the study period, which lasted from June 2022 until February 2021, Water samples were collected for analysis, , in addition to field measurements of some physical and chemical factors (temperature - salinity). Phytoplankton abundance, The concentrations of nutrient (NO₃, PO₄, SIO₄). The highest concentrations of phosphate ions were observed at station St-A (close to the sewage) , while the highest concentrations of nitrate ions were registered in Winter, The results showed high values of concentrations of phosphate In the summer Accompanied by similar temperature and salinity in the two sites. Nutrient concentrations decreased with distance from the downstream point. Values of the total abundance ranged between 2320-9786 cell/L.This study has recorded 82 species of phytoplankton in study sites, distributed as follow: (60) species of Diatoms, (17) species of Dinoflagellates, , and 2 species of Cyanophyta, and (3) species of Chlorophyta